Purification of antibacterial compounds from spathiphyllum cannifolium leaf - Ahmad Raus, Raha; Abdullah, Erlina; Jamal, Parveen; Jimat, Dzun Noraini (2013)
Spathiphyllum cannifolium is an ‘araceae’ species which can be found in Malaysia for landscaping. Previous study carried out in this lab found that this plant possesses the highest antibacterial activity among 19 flowering plants screened. In the present study, purification of antibacterial compound of the plant was conducted. For purification of antibacterial compound, open column chromatography was conducted and ethyl acetate, hexane and ethanol are used as the mobile phase. The results showed that the elution of column with 80% ethyl acetate in ethanol provide fractions with the highest antibacterial activity. The fractions were analyzed with TLC plates and revealed a single spot under UV light at 0.85 Rf value. Further purification of the single spot using HPLC showed two isolated compounds at retention time of 5.53 minutes and 8.26 minutes were obtained. The compounds were suspected as flavanoids as they can be detected at wavelength 360 nm and 400 nm.